Systematic Review on Improving Performance of a Single-Spool Gas Turbine System Using Combustion Chamber Direct Water Injection (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study synthesizes prior research on performance enhancement of single-spool gas turbine systems through direct water injection in the combustion chamber. The review establishes that water injection effectively reduces nitrogen oxides (NOx) emissions by suppressing peak flame temperatures and modifying combustion kinetics. Numerical and experimental investigations indicate that increasing water-to-fuel ratios improves combustion stability, augments mass flow rate, and enhances power output, albeit with a corresponding rise in specific fuel consumption. Comparative assessment of alternative optimization strategies, including regeneration, combined cycles, and inlet air cooling, reveals inherent trade-offs between efficiency gains, environmental performance, and operational constraints. Despite extensive studies, a critical gap remains in defining optimal injection parameters under varying operating conditions. This work therefore proposes a simulation-based framework for optimizing water injection in a 135 MW single-spool gas turbine, targeting improved thermal efficiency, reduced emissions, and enhanced overall performance.